PEMBERDAYAAN MASYARAKAT PULAU SARAPPO LOMPO DALAM UPAYA KONSERVASI LINGKUNGAN PESISIR DI DESA MATTIRO LANGI, KECAMATAN LIUKANG TUPABBIRING, KABUPATEN PANGKEP, SULAWESI SELATAN - Nurhalilah, Nurhalilah; Yunus, Rabina; Rusli, A.M. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to understand the process of empowering coastal communities through environmental conservation using a Participatory Action Research (PAR) approach linked with Islamic daʿwah. The research was conducted in Mattiro Langi Village, Sarappo Lompo Island, Pangkep, South Sulawesi, in response to coastal ecosystem degradation caused by household waste. The empowerment strategy was carried out through stages of social mapping, environmental education, formation of PKK mothers’ groups as pioneers of environmental awareness movements, and policy advocacy based on community participation. Throughout the process, a dialogical approach was used to build collective awareness, facilitate critical reflection, and create social transformation through beach clean-up actions, plastic waste management training, and the strengthening of ecological daʿwah. The results indicate an increase in community participation, the emergence of local leaders, and a shift in the community’s paradigm regarding the importance of environmental conservation. This article affirms that integrating participatory approaches, Islamic values, and environmental conservation can serve as a model for sustainable empowerment in coastal areas. The success achieved also forms the basis for recommendations to scale up the program with the support of village institutions.